Evaluation of hydraulic properties and climatic conditions of Yaychi area Southwest of Kirkuk - North of Iraq - Al-Kubaisi, Qusai Y.; Khorsheed, Sabah Ahmed (Iraqi Journal of Science, 2018)
This study includes determining the climatic conditions and the nature of the reservoirs in the region with the determination of the flow direction and the hydraulic characteristics of the aquifer. The meteorological data for the Kirkuk station for the period 1971-2015 showed that the values of the monthly rates of temperature, precipitation, evaporation, relative humidity, wind speed and Sunshine duration are (9.1 to 36.2 C), (0.03 to 65.8 mm), (51.4 to 412.7mm), (21.7 to 71.1%), (1.3 to 2.1 m / s), and (5.4 to 11.2 hour) respectively. And according to the annual rainfall rate is (348.13mm), found 18 years of the climatic period are wet years and 27 years are dry years. Thornthwait method was used to calculate the values of Potential Evapotraspiration (PE) then determine the annual value of WS and WD which equal 238.4mm and 852.8mm respectively. The study showed the existence of a shallow aquifer unconfined in the Quaternary deposits with the presence aquifer confined in the Bai-Hasan Formation. The flow net map is shown by mainly that the groundwater flow in the area, it is from the northeastern parts towards the southwestern parts. The information of single pumping test for five wells in the study area shows that the values of the transmissivity (T), hydraulic conductivity (K) and specific capacity (SC) were ranged from (88.1 to 829.7m2/d), (0.64 to 8.74m/d) and (33.28 to 295.75m2/d) respectively, where (T) and (K) calculated by using (AQTESOLV 4.5) software that depend on the methods of Cooper-Jacob and Theis recovery for analysis these information.